Enhancing post-thaw sperm quality in rams: quinic acid as a natural antioxidant - Denk, Barış; Kırıkkulak, Murat; Güngör, Şükrü; Gülhan, Mehmet Fuat; İnanç, Muhammed Enes; Avdatek, Fatih; Yeni, Deniz; Taşdemir, Umut (Frontiers in Veterinary Science, 2026)
IntroductionThis study investigated the effects of quinic acid (QA) supplementation at different concentrations (Control, 50, 100, and 200 μg/mL) on the post-thaw quality of ram semen, with a focus on motility, DNA integrity, flow cytometric parameters, and oxidative status.Materials and methodsA total of 40 ejaculates collected from Ramlic rams were cryopreserved using Tris-based extenders containing QA. Post-thaw sperm quality was evaluated using Computer-Assisted Sperm Analysis (CASA), flow cytometry assays for viability, mitochondrial activity, and lipid peroxidation, and the single cell gel electrophoresis (COMET) analysis for DNA integrity. Oxidative status was assessed through measurements of TAS, TOS, MDA, and OSI.ResultsQA supplementation at 100 μg/mL significantly improved total and progressive motility and enhanced key kinematic parameters compared with the control group (p < 0.05). Flow cytometry analyses showed that spermatozoa treated with 100 μg/mL QA exhibited higher viability (SYBR+; 81.54 ± 2.64%) and high mitochondrial membrane potential (HMMP; 26.98 ± 2.25%), along with reduced lipid peroxidation (BODIPY+; 35.72 ± 4.58%) relative to the control (p < 0.05). COMET assay results indicated that QA treatment, particularly at 100 μg/mL, decreased tail length and tail moment values, signifying reduced DNA fragmentation. Regarding redox balance, 100 μg/mL QA significantly enhanced total antioxidant status (TAS; 1.45 ± 0.01 μmol/L) and lowered oxidative stress index (OSI; 58.96 ± 2.44) compared to control (p < 0.001). However, the highest dose (200 μg/mL) increased malondialdehyde (MDA; 58.90 ± 0.17 nmol/mL) and total oxidant status (TOS; 11.20 ± 0.80 mmol/L), indicating a possible pro-oxidant effect at excessive concentrations.ConclusionIn conclusion, QA exerted dose-dependent protective effects on sperm motility, viability, HMMP, and DNA stability during cryopreservation. The optimal concentration (100 μg/mL) effectively mitigated oxidative stress and improved post-thaw semen quality, suggesting that QA could serve as a promising antioxidant and cryoprotective additive for enhancing the success of artificial insemination programs in rams.